2011
DOI: 10.1038/nrd3358
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic potential of targeting endogenous inhibitors of nitric oxide synthesis

Abstract: Asymmetric dimethylarginine (ADMA)--a naturally occurring amino acid that is a product of protein breakdown--is released into the cytoplasm following the post-translational methylation of arginine residues within proteins and the subsequent proteolysis of these arginine-methylated proteins. ADMA inhibits all three isoforms of nitric oxide synthase and therefore has the potential to produce diverse biological effects, particularly in the cardiovascular system. In addition to its renal clearance, endogenously pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
161
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(162 citation statements)
references
References 193 publications
0
161
0
1
Order By: Relevance
“…Based on tissue messenger ribonucleic acid (mRNA) levels, it has been suggested that the expression pattern of DDAH 1 overlaps more closely with the expression pattern of neuronal NOS, whereas DDAH 2 expression has greater similarities with endothelial NOS expression [26,27]. However, it is still unclear which DDAH isoform represents the principal methylarginine-metabolizing enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on tissue messenger ribonucleic acid (mRNA) levels, it has been suggested that the expression pattern of DDAH 1 overlaps more closely with the expression pattern of neuronal NOS, whereas DDAH 2 expression has greater similarities with endothelial NOS expression [26,27]. However, it is still unclear which DDAH isoform represents the principal methylarginine-metabolizing enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the gene for DDAH is evolutionarily well conserved suggests that the enzyme confers an important survival advantage [10]. And it can be postulated that genetic variations in DDAH that affect the ability of the enzyme to metabolize ADMA might increase cardiovascular risk in patients with renal failure and might also determine, in part, the rate of disease progression [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because nitric oxide is essential for cellular signalling, it is involved in many physiological and pathological processes including inflammation (Leiper & Nandi, 2011), protection of liver ischemic damage (Yang et al, 2011), carcinogenesis and rheumatoid arthritis (Melchers et al, 2006). Therefore, inhibition of nitric oxide may suggest the mechanism of saponin against inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals there are three methylarginine species, ADMA, symmetrical dimethyarginine (SDMA) and L-NMMA. ADMA and L-NMMA competitively inhibit arginine binding to NOS and reduce NO production 20,21 . SDMA does not inhibit the activity of the NOS enzymes 22 .…”
Section: Introductionmentioning
confidence: 99%